Simultaneous Estimation of Ibuprofen and Phenylephrine Hydrochloride in Bulk and Combined Dosage Form by First Derivative UV Spectrophotometry Method - Mehul Patel; Bhavna Patel; Shraddha Parmar (Journal of Spectroscopy)
A simple, precise, rapid, and economic method was developed for the simultaneous determination of Ibuprofen and Phenylephrine HCl in bulk and combined dosage form. This method involves first-order derivative spectroscopy using 248 nm and 237 nm as zero crossing points for Ibuprofen and Phenylephrine HCl, respectively. For spectrophotometric method 0.1 N NaOH was used as a solvent. The linearity was established over the concentration range of 12–72 μg/mL and 1.5–22 μg/mL for Ibuprofen and Phenylephrine HCl with correlation coefficient (r2) of 0.9972 and 0.9981, respectively. The mean % recoveries were found to be in the range of 98.88% and 98.54% for Ibuprofen and Phenylephrine HCl, respectively. Interday and intraday studies showed repeatability of the method. The method was found to be specific and robust. The method was successfully applied to pharmaceutical formulation, with no interference from excipients as indicated by the recovery study. Results of analysis were validated statistically and by recovery studies.